Peran Kelompok Pengrajin Pandan Baiduri dalam Pelestarian Anyaman Lapik Terawang di Desa Koto Dian 2004-2024 - Nurul Afifah; Abdul Salam (YASIN, 2026)
Anyaman Lapik Terawang is a cultural heritage of the Koto Dian Village community that has social, economic, and local identity values. This study aims to describe and analyze the role of the Pandan Baiduri Artisan Group in preserving Anyaman Lapik Terawang during the 2004–2024 period. This study used a qualitative approach with the historical method. Data were collected through semi-structured interviews, observation, documentation studies, group archives, Intangible Cultural Heritage designation documents, and material evidence in the form of Anyaman Lapik Terawang products. Semi-structured interviews were conducted using open-ended question guidelines that allowed informants to explain their experiences, knowledge, and perspectives in depth. The data were analyzed through the stages of the historical method, including heuristics, source criticism, interpretation, and historiography. The results showed that the Pandan Baiduri Artisan Group played an important role in organizing production, preserving traditional techniques and motifs, transmitting skills through direct practice, developing product variations, expanding marketing, and strengthening cultural recognition through the designation of Intangible Cultural Heritage and Communal Intellectual Property. The conclusion of this study emphasizes that the sustainability of Anyaman Lapik Terawang depends heavily on the active role of artisan groups, skill regeneration, availability of raw materials, and institutional support. The implications of this study indicate the importance of strengthening artisan groups as key actors in preserving local culture and developing community-based traditional crafts.